Poor validity of functional performance tests to predict knee injury in female soccer players with or without anterior ruciate ligament reconstruction - Fältström, A.; Hägglund, M.; Hedevik, H.; Kvist, J. (The American Journal of Sports Medicine, 2021)
Background: Various tests have been developed to evaluate athletes` functional performance and for use as screening tools for injury prediction. Further validation of their accuracy to predict injury is needed.